Analisis Dampak Keterampilan, Pengalaman Kemampuan Pegawai Terhadap Pengujian Kendaraan Bermotor (PKB) pada Unit Pelayanan Pengujian Kendaraan Bermotor Dinas Perhubungan Kabupaten Dairi - Mutiara Simangunsong; Anton A. P. Sinaga; Junika Napitupulu (Universitas Methodist Indonesia, 2026)
The purpose of this study was to determine and analyze the impact of employee skills, experience and abilities on motor vehicle testing services (PKB) at the motor vehicle testing service unit of the Dairi Regency Transportation Service. The data type is quantitative descriptive with a sample of 52 respondents. This research concludes that Skills have a partial positive and significant effect on Motor Vehicle Testing (PKB) at the Motor Vehicle Testing Service Unit of the Dairi Regency Transportation Service. Partial experience has a positive and significant effect on Motor Vehicle Testing (PKB) at the Motor Vehicle Testing Service Unit of the Dairi Regency Transportation Service. Employee abilities partially have a positive and significant effect on Motor Vehicle Testing (PKB) at the Motor Vehicle Testing Service Unit of the Dairi Regency Transportation Service. Based on the results of multiple regression tests, t tests, f tests, and determination, the results of this research show that employee skills, experience and abilities have a positive and significant effect on motor vehicle testing (PKB) at the Motor Vehicle Testing Service Unit of the Dairi Regency Transportation Service. The results of the analysis of the coefficient of determination R Square (R2) Skills, Experience, and Ability of Employees Able to Influence Motor Vehicle Testing (PKB) amounted to 47.2% while the remaining 52.8% was influenced by other factors not examined in this research.